Discovering the Comic in Don Quixote - Gillman, Laura, 1952- (Book collections on Project MUSE., 1993)
Gorfkle challenges the assumption that the comic is inferior to the tragic as a vehicle for expressing serious thought and the belief that the comic has only a secondary function in Cervantes's Don Quixote. She systematically surveys the comic mechanisms of the novel from the perspectives of the contemporary literary theories of Bakhtin, Girard, and Derrida.